Parametric Optimization Of Daylight And Thermal Performance Through Louvers In Hot And Dry Climate Of Tehran - Mahdavinejad, M.; Mohammadi, S. (University of Eloued جامعة الوادي, 2016)
This article describes a parametric research simulated different louver conditions performance under given climate. The DIVA (Design, Iterate, Validate and Adapt) plug-in for Rhinoceros/Grasshopper software is used as the main tool, given its ability to effectively calculate daylight metrics (using the Radiance/Daysim engine) and energy consumption (using the EnergyPlus engine). The optimization process is carried out parametrically controlling the shadings’ geometries. Genetic Algorithms (GA) embedded in the evolutionary solver Octopus is adopted in order to achieve close to optimum results by controlling iteration parameters. The results of the paper show that there are meaningful optimum parameters which may help for better thermal performance through louvers in hot and dry climate of Tehran. The results indicate impressive efficiency in building industry in contemporary architecture of developing countries especially in Iran and west of Asia.
Article in Journal of Fundamental and Applied Sciences Vol 08, N 03
Keywords: Daylight, Thermal, louver, Shading, Optimization